An evaluation of Sargassum cinctum anticancer properties utilizing in vitro testing and molecular docking, with assistance from GC-HRMS and FTIR - Mohini Salunke, Preeti Mane, Smita Kumbhar, Balaji Wakure (Journal of Applied Pharmaceutical Science, 2024)
Cancer is characterised by unregulated, uncontrollable cell development, which is a continuous abnormality in cellular behavior. This frequently results in the aggressive invasion, metastasis, and dispersal of malignant cells throughout different organs. Breast cancer is one of the most common types of cancer that is prevalent worldwide. In particular, it comes in second place after lung cancer in terms of cancer-related mortality among women. The current work concentrated on identifying bioactive components in ethanolic extracts of Sargassum cinctum by gas chromatography high-resolution mass spectroscopy (GC-HRMS) and Fourier-transformed infrared (FTIR) analysis. Following GC-HRMS and FT-IR studies, anticancer activity and molecular docking are carried out on the ethanolic extract of S. cinctum. Different bioactive compounds, including phenols, alcohols, amines, aldehydes, ketone esters, carboxylic acids, alkenes, and alkanes, are detected by the GC-HRMS and FT-IR analyses. Sargassum cinctum ethanolic extract exhibits strong anti-cancer properties. The IC50 value of the MCF 7 cell line and A549 cell line is 134.50 and 161.02 μg/ml, respectively. Asn923, Phe1047, Lys868, and Asp1046 from vascular endothelial growth factor receptor (VEGFR) and Met623, Asp690, and Lys567 from anexelekto (AXL) kinase are among the residues that may have contributed to the anti-cancer benefit observed in this study. Using in-silico approach, it was determined that the medications that target the VEGFR2 and AXL kinase receptors had anticancer properties. This is the first-hand evaluation of the bioactive elements of S. cinctum extracts that have anticancer potential, as far as we aware. Recent study proved value of in silico analyses in the search for new drugs and the capacity of marine compounds to produce distinctive bioactives with considerable biological activity.
Keywords: Sargassum cinctum, GC-HRMS, FT-IR, anticancer, docking studies